Dance, Interactive Technology, and the Device Paradigm. (25th March 2014) - Mullis, Eric
<x content-type="archive" xml:space="preserve">Abstract</x> Dance artists often suggest that working with interactive technology can produce the experience of bi-directionality in which the performer is perceptually aware of the manner in which movement directly produces changes in the performance environment. In addition, it is suggested that the performer can also become aware of the manner in which the technologies affect the dancer's performance. Drawing on phenomenology, some have argued that experiences of bi-directionality call for a reconsideration of the manner in which the moving body interacts with technological devices. I draw on Albert Borgmann's philosophy of technology to examine this approach and argue that it overlooks important issues concerning contextuality and the nature of the technological devices that are utilized in interactive performance.